The inclination of information and communication technology (ICT) students towards entrepreneurship - Mior Nazri, Mior Nasir; Hamid, Zarinah; Muslim, Herna (Pak Publishing Group, 2014)

(untitled)
The lack of innovation in human capital in terms of quality and quantity as well as the significant brain drain has retarded the progress of Malaysia towards becoming a developed country by 2020. In view of this situation, the Ministry of Higher Education (MoHE) of Malaysia has assigned the National Coordination Taskforce for Innovation (NCTI) to develop an innovative human capital (IHC) at tertiary level. One of the key elements in the IHC implementation plan is to enhance the entrepreneurial skills through education. The objective of this study is to investigate the perception and reception of non-business students on entrepreneurship education at the Faculty of Information and Communication Technology (ICT) of International Islamic University Malaysia (IIUM). It examines the level of students‟ inclination towards becoming entrepreneurs and their interest to learn entrepreneurial skills. The survey utilizes 96 usable responses of third and fourth year students from the faculty. The primary data consists of a set of survey questionnaires which include entrepreneurial intention, attitude towards entrepreneurship, subjective norms of entrepreneurship, perceived behavioral control over entrepreneurship, the influence of faculty on entrepreneurial behavior and the entrepreneurship learning propensity. It provides some insights on the factors influencing ICT students to venture into entrepreneurship. It also suggests measures on the importance of graduates to become successful entrepreneurs and be less dependent on employers. Keywords: Entrepreneurship, Inclination of students, Entrepreneurial skills